2016
DOI: 10.1080/00918369.2016.1150045
|View full text |Cite
|
Sign up to set email alerts
|

Lesbians and Gay Men’s Vacation Motivations, Perceptions, and Constraints: A Study of Cruise Vacation Choice

Abstract: This study explores the push-pull vacation motivations of gay male and lesbian consumers and examines how these underpin their perceptions and purchase constraints of a mainstream and LGBT(1) cruise. Findings highlight a complex vacation market. Although lesbians and gay men share many of the same travel motivations as their heterosexual counterparts, the study reveals sexuality is a significant variable in their perception of cruise vacations, which further influences purchase constraints and destination choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Four of the included studies had MSM focus. and connotations (pull) 111 . Thereby, travelling can function as a finite province of meaning; a distinct break from the everyday life where you can be different and act differently than at home 109,112 .…”
Section: Sexual Risk Taking Behaviour While Travelling Abroadmentioning
confidence: 99%
“…Four of the included studies had MSM focus. and connotations (pull) 111 . Thereby, travelling can function as a finite province of meaning; a distinct break from the everyday life where you can be different and act differently than at home 109,112 .…”
Section: Sexual Risk Taking Behaviour While Travelling Abroadmentioning
confidence: 99%
“…Travel constraints are described as factors that restrict the development of a tourism market and limit the potential of tourism destination development (H. J. Chen, Chen, and Okumus 2013), as they are, in fact, "reasons that limit or prevent participation or that explain why people have stopped in taking part in leisure-related activities" (Weeden, Lester, andJarvis 2016, p. 1069). Most of the literature regarding travel constraints is based on the conceptualization of leisure constraints, proposed by Crawford and Godbey (1987), and modified in 1991 (Crawford, Jackson, and Godbey 1991).…”
Section: Constraints and Lgbt Travelmentioning
confidence: 99%
“…Studies have suggested that lesbian, gay, bisexual, transgender (LGBT) individuals whose sexual identity can be easily identified face higher victimization levels and, ultimately, constraints than other groups of travelers (Brunt and Brophy 2006). These are believed to limit and/or prevent them from partaking in travel activities (Weeden, Lester, and Jarvis 2016). A national survey carried out by the British government in 2017 confirmed that most of the severe incidents members of the LGBT community experienced went unreported, especially if these involved people they lived with (94%).…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is evidence that millennials' vacation habits are not the same as previous generations' (Alton, 2017; Loman, 2017) so studying age could prove fruitful. Along with age and gender, previous research (Weeden et al, 2016) has identified particular vacation habits based on sexual preference. Distinguishing demographic variables such as these will shed more light on the effectiveness of vacation policy on different types of workers.…”
Section: Implications For Future Researchmentioning
confidence: 99%